(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2023)
Introduction In the dynamic landscape of higher education, where the pursuit of knowledge often intertwines with rigorous academic demands, understanding and effectively managing stress have become crucial components of students’ overall well-being. In this context, this study emerged as a pertinent exploration. Carried out during the initial semester of the academic year 2020-2021, this study delves into the experiences of fourth-year criminology students at CICOSAT Colleges, aiming to unveil the multifaceted facets of stress they encounter. The primary objectives encompass investigating the origins of stress within this specific academic cohort, discerning the impact of stress on their academic achievements, and unearthing the array of strategies they employ to confront and mitigate stress. By venturing into this domain, the researchers aspire to offer meaningful insights into stress management, providing a valuable resource for the academic institution and the broader educational community. Situated within the confines of the Criminology Department at CICOSAT Colleges in San Fernando City, La Union, the study encapsulates the experiences of these students over the semester, encapsulating their endeavors from August through December. Method The study utilized a qualitative research design, focusing on fourth-year criminology students as respondents. Data collection involved interviews conducted through Google Forms and messenger chats, ensuring individual engagement. Participants’ experiences were gathered to understand stressors and coping strategies comprehensively. Results and Discussion Stressors in Academic Context: Academic requirements emerged as a significant challenge among the reported stressors. Students faced stressors like meeting deadlines, managing excessive requirements, navigating online learning tools, and comprehending complex subjects. The overwhelming demands often led to stress, hindering their ability to complete assignments effectively. Some students encountered technical issues related to online learning, such as poor internet connections and device limitations. Stressors in Personal and Family Context: Beyond academic pressures, personal and family variables were identified as additional stressors. Financial difficulties and family problems were reported, exerting considerable stress on the students. Conclusion and Recommendation Based on the study’s findings, several conclusions were drawn: • Financial and family variables, social and interpersonal relationships, and academic requirements were the primary stressors among college students. • Stressors notably impacted students’ academic performance, often leading to reduced focus and inadequate coping strategies for managing academic demands. • Relaxation and entertainment activities were common coping mechanisms used by students to combat stress. • Effective coping strategies positively influence students, motivating them to put in more effort to manage stress and achieve their academic goals. In light of the study’s conclusions, the following recommendations are offered: • Students are encouraged to discover appropriate coping strategies to alleviate anxiety, such as meditation and mindfulness techniques. Incorporating short breaks into their routines can help maintain physical and mental well-being. • Students should adopt a broader perspective, recognizing that individual actions taken today can prevent long-term consequences. Breaking the cycle of stress, worry, and poor health involves healthy habits like staying hydrated, eating nutritious foods, exercising regularly, and ensuring adequate sleep. • Utilize support systems, including family, friends, school guidance counselors, and teachers, to reach out when stressed. • CICOSAT Colleges could implement the proposed stress management program to assist students in effectively managing stress and achieving their life goals. By addressing stressors and promoting effective coping strategies, students can navigate their academic journeys with resilience, ultimately fostering better mental and emotional well-being.